2013
DOI: 10.5230/jgc.2013.13.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Lymph Node Metastasis in Signet Ring Cell Gastric Cancer and the Feasibility of Endoscopic Submucosal Dissection

Abstract: PurposeEndoscopic submucosal dissection has recently been practiced on a differentiated type of early gastric cancer. However, there is no clear evidence for endoscopic treatments of signet ring cell carcinoma. The aim of this study is to identify the predictive clinicopathological factors for lymph node metastasis in signet ring cell carcinoma for assisting endoscopic submucosal dissection trials.Materials and MethodsA total of 186 patients with early signet ring cell carcinoma who underwent radical curative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Although we found that the female gender was an independent risk factor for metastasis, many studies have not related patient gender with lymph node involvement. [19][20][21]24,28 Kim et al 16 found that male gender was a risk factor for metastasis whereas several authors 7,62,63 have detected that female gender was significantly and independently related to metastasis as a result in line with ours. Although the link between gender and aggressive tumor behavior in EGC is still unclear, these authors have suggested that the endogenous estrogen levels might have an effect on more aggressive tumor behavior in females by promoting tumor growth.…”
Section: Discussionsupporting
confidence: 93%
“…Although we found that the female gender was an independent risk factor for metastasis, many studies have not related patient gender with lymph node involvement. [19][20][21]24,28 Kim et al 16 found that male gender was a risk factor for metastasis whereas several authors 7,62,63 have detected that female gender was significantly and independently related to metastasis as a result in line with ours. Although the link between gender and aggressive tumor behavior in EGC is still unclear, these authors have suggested that the endogenous estrogen levels might have an effect on more aggressive tumor behavior in females by promoting tumor growth.…”
Section: Discussionsupporting
confidence: 93%
“…Compared to well-differentiated intestinal-type early adenocarcinoma, intramucosal signet ring cell carcinoma has been found to have a similar incidence of submucosal spread, lymphovascular invasion, and nodal metastasis [30,31]. Since Hyung et al [27] reported a very low (1.6%, 3/185) rate of nodal metastasis for signet ring cell carcinoma at the pT1a stage, a number of studies have confirmed this finding (Table 1) [27,28,29,30,31,32,33,34,35,36,37,38,39]. The average frequency of nodal metastasis (based on the data listed in Table 1) is only 4.2% for intramucosal signet ring cell carcinoma, over 5-fold less for signet ring cell carcinoma with submucosal invasion (23%), which has been confirmed by logistic regression analysis of nodal metastasis frequency in early signet ring cell carcinoma between intramucosal and submucosal invasion [39,40].…”
Section: Low Risk Of Nodal Metastasis For Intramucosal Signet Ring Cesupporting
confidence: 52%
“…However, recent clinicopathology studies have shown contrasting evidence for intramucosal signet ring cell carcinoma that arises in the isthmus/neck of a gastric unit and is more common in young women, distal stomach with flat and depressed growth patterns [27,28,29,30,31]. A significantly better 5-year overall survival rate has been reported in patients with early signet ring cell carcinoma than in those with non-signet ring cell carcinoma at the same stage [32,33].…”
Section: Low Risk Of Nodal Metastasis For Intramucosal Signet Ring Cementioning
confidence: 99%
“…[1,2] Although categorized as undifferentiated histology, early gastric SRC has a low rate of lymph node metastasis (LNM) similar to the differentiated cancer. [35] Several studies revealed no LNM when SRC lesions were confined to mucosa, without lymphovascular invasion (LVI), and less than 15 [6] or 20 mm. [7] Recently, Pyo et al [8] introduced a risk-scoring tool for gastric mucosal SRC.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, endoscopic submucosal dissection (ESD) has been indicated for early gastric SRC to maintain the quality of life in East Asia. [6,9] However, most studies only focused on identifying predictive factors associated with LNM, and failed to provide a quantified risk of LNM for individuals. [610] Moreover, the clinical performance between different treatment strategies has not been assessed yet.…”
Section: Introductionmentioning
confidence: 99%